Positive electrode active material and lithium secondary battery including same

By dividing lithium-rich lithium manganese-based oxides into small particles and large particles and forming a barrier layer on their surface, the problem of insufficient energy density and stability of lithium-rich lithium manganese-based oxides in lithium secondary batteries is solved, and higher electrochemical performance and longer life are achieved.

CN119864389APending Publication Date: 2025-04-22ECOPRO BM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411349529.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-20
Filing Date
2024-09-26
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The lithium-rich lithium manganese-based oxides used in existing lithium secondary batteries have problems with insufficient energy density per unit volume and stability, especially in terms of electrochemical performance and rate performance.

Method used

By dividing the lithium-rich lithium manganese-based oxide into small particles and large particles, a positive electrode active material with a bimodal particle size distribution is formed, and a barrier layer is formed on the surfaces of the small particles and large particles to inhibit the dissolution of the transition metal.

Benefits of technology

The unit volume energy density of lithium-rich lithium manganese-based oxides is improved, and the electrochemical performance and stability is improved, the resistance of the negative electrode is reduced, and the life of the lithium secondary battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005061941750000351
    Figure BDA0005061941750000351
  • Figure BDA0005061941750000371
    Figure BDA0005061941750000371
  • Figure BDA0005061941750000381
    Figure BDA0005061941750000381
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material and a lithium secondary battery comprising the same, and more particularly, to a bimodal positive electrode active material for improving low energy density per unit volume and stability of a lithium-rich lithium manganese-based oxide, and a lithium secondary battery comprising the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material and a lithium secondary battery comprising the same, and more particularly to a bimodal positive electrode active material for improving the low unit volume energy density and stability of lithium-rich lithium manganese-based oxides and a lithium secondary battery comprising the same. Background Art

[0002] Batteries use materials that can undergo electrochemical reactions at the positive and negative electrodes to store electrical energy. A typical example of such batteries is a lithium secondary battery that stores electrical energy through the chemical potential difference when lithium ions are inserted / released between the positive and negative electrodes.

[0003] The lithium secondary battery is prepared by using a substance capable of reversibly inserting and extracting lithium ions as a positive electrode active material and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.

[0004] Representative materials used as positive electrode active materials for lithium secondary batteries include lithium composite oxides. Examples of the lithium composite oxides include LiCoO2, LiMn2O4, LiNiO2, LiMnO2, or complex oxides of nickel, cobalt, manganese, or aluminum.

[0005] Among the above-mentioned positive electrode active materials, LiCoO2 is the most widely used due to its excellent life characteristics and charge and discharge efficiency, but its price competitiveness is limited due to the resource limitation of cobalt used as a raw material and its high price.

[0006] Lithium manganese-based oxides such as LiMnO2 and LiMn2O4 have the advantages of excellent thermal stability and low price, but have problems of small capacity and poor high temperature characteristics. In addition, LiNiO2-based positive electrode active materials have battery characteristics of high discharge capacity, but due to the cation mixing problem between lithium and transition metals, they are difficult to synthesize, resulting in major problems in rate performance.

[0007] Furthermore, depending on the severity of such cation mixing, a large amount of lithium byproducts are generated, most of which include LiOH and Li2CO3, so when preparing the positive electrode slurry, it leads to gelation, or after preparing the electrode, it may become a cause of gas generation due to repeated charge and discharge. In addition, the residual Li2CO3 in the above lithium byproducts increases the swelling phenomenon of the monomer and becomes a cause of reducing the service life.

[0008] Various candidate materials are being discussed for compensating for the shortcomings of these existing positive electrode active materials.

[0009] For example, research is underway to use lithium-rich manganese-based oxides containing excess manganese in transition metals and a lithium content greater than the total content of transition metals as positive electrode active materials for lithium secondary batteries. Such lithium-rich manganese-based oxides are also called overlithi ated layered oxides (OLO).

[0010] Although the above OLO has the advantage of showing high capacity under high voltage working environment in theory, in reality, due to the excessive manganese contained in the oxide, its conductivity is relatively low, so there is a disadvantage that the rate performance of the lithium secondary battery using OLO is low. As mentioned above, when the rate performance is low, the charge / discharge capacity and life efficiency (cycle capacity retention) deteriorate during the cycle of the lithium secondary battery.

[0011] Furthermore, a disadvantage of OLO is that due to the characteristics of the material, the porosity in the particles is high, and thus the energy density per unit volume is low.

[0012] In order to solve the above problems, research has been conducted to change the composition of OLO, but these attempts have not yet reached commercialization level. Summary of the invention

[0013] Technical issues

[0014] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles plays a leading role in the market, and the demand for positive electrode active materials used in lithium secondary batteries is also constantly changing.

[0015] For example, in the related art, lithium secondary batteries using lithium iron phosphate (LFP) are mainly used from the viewpoint of ensuring safety, etc., but recently, the use of nickel-based lithium composite oxides having a large energy capacity per unit weight compared with LFP has been expanded.

[0016] In addition, nickel-based lithium composite oxides, which are mainly used as positive electrode active materials for high-capacity lithium secondary batteries in recent years, must use ternary metal elements such as nickel, cobalt and manganese or nickel, cobalt and aluminum. However, since cobalt is not only unstable in supply and demand but also too expensive compared to other raw materials, a positive electrode active material with a new composition that can reduce the cobalt content or does not contain cobalt is needed.

[0017] Taking the whole situation into consideration, although lithium-rich lithium manganese-based oxides can meet the expectations of the above-mentioned market, the above-mentioned lithium manganese-based oxides still have the limitation of lacking electrochemical performance or stability in replacing commercial positive electrode active materials such as ternary lithium composite oxides composed of nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA).

[0018] For example, as mentioned above, OLO has a low energy density per unit volume due to its material composition (including excess lithium) and structural characteristics (high porosity in the particles).

[0019] However, the inventors of the present invention have confirmed that the low unit volume energy density of the lithium-rich lithium manganese-based oxide can be improved by preparing the above-mentioned lithium manganese-based oxide by dividing the above-mentioned lithium manganese-based oxide into small particles and large particles and then providing a positive electrode active material having a bimodal particle size distribution as a mixture of the above-mentioned small particles and the above-mentioned large particles.

[0020] Therefore, an object of the present invention is to provide a positive electrode active material with a bimodal particle size distribution for improving the low unit volume energy density of lithium-rich lithium manganese-based oxides.

[0021] In addition, the inventors of the present invention have confirmed that even if the existing lithium-rich lithium manganese-based oxides have disadvantages in electrochemical performance and / or stability compared to other types of commercialized positive electrode active materials, when inducing the selective growth of primary particles that constitute small particles in the above-mentioned positive electrode active material with a bimodal particle size distribution, the lithium-rich lithium manganese-based oxides can also exert electrochemical performance and stability at a commercializable level.

[0022] Therefore, an object of the present invention is to provide a positive electrode active material, which is a positive electrode active material with a bimodal particle size distribution including small particles and large particles in order to improve the low unit volume energy density of lithium-rich lithium manganese-based oxide, and which can reduce the side reactions caused by the high specific surface area of ​​small particles relative to large particles by inducing the selective growth of primary particles of the above-mentioned small particles.

[0023] On the other hand, the inventors of the present invention have confirmed that lithium manganese-based oxides are more likely to have transition metals eluted from the particle surface during repeated charge / discharge than ternary lithium composite oxides. In particular, manganese contained in excess in lithium manganese-based oxides is more likely to be eluted from the particle surface.

[0024] When the transition metal is eluted from the lithium manganese-based oxide, the eluted transition metal may react with the electrolyte on the surface of the lithium manganese-based oxide to form impurities. The impurities not only increase the surface resistance of the lithium manganese-based oxide, but also become the cause of reducing the insertion / extraction efficiency of lithium ions through the lithium manganese-based oxide.

[0025] Furthermore, transition metals dissolved from the above-mentioned lithium manganese-based oxide or impurities formed by the reaction of the dissolved transition metals with the electrolyte may move to the negative electrode through the electrolyte as a medium and may be deposited on the surface of the negative electrode.

[0026] For example, due to a side reaction between the surface of the lithium manganese-based oxide and the electrolyte or a structural change (crystal structure change, etc.) of the lithium manganese-based oxide, the excessive amount of Mn contained in the lithium manganese-based oxide may be 2+ Mn dissolved in the electrolyte may be dissolved in the electrolyte. 2+ During the formation or charge-discharge process, the electrolyte may move to the negative electrode surface, thereby reacting with various substances (electrons, electrolyte, electrodes or by-products, etc.) present in the battery. As a result, Mn 2+ , Mn metal or Mn-containing compounds (e.g., MnCO3, MnO, MnF2, etc.) impurities exist.

[0027] Transition metals or impurities deposited on the surface of the negative electrode will rapidly increase the resistance of the negative electrode. This resistance anomaly is a representative cause of accelerated deterioration of the life of lithium secondary batteries.

[0028] In particular, in the case of a lithium secondary battery using the above-mentioned lithium manganese-based oxide as a positive electrode active material, the operating voltage is higher than that of a lithium secondary battery using other commercially available ternary lithium composite oxides as a positive electrode active material, so the above-mentioned problem is likely to occur.

[0029] However, there is currently no technology for addressing the dissolution of transition metals from lithium-rich lithium manganese-based oxides and the problems arising therefrom.

[0030] Therefore, an object of the present invention is to provide a positive electrode active material, which is a positive electrode active material with a bimodal particle size distribution including small particles and large particles in order to improve the low unit volume energy density of lithium-rich lithium manganese-based oxide, and which suppresses or reduces the dissolution of transition metals from the above-mentioned lithium manganese-based oxide by covering the surfaces of the small particles and the large particles with a barrier layer.

[0031] In addition, another object of the present invention is to provide a lithium secondary battery using the positive electrode active material defined herein.

[0032] The purpose of the present invention is not limited to the purpose mentioned above, and other purposes and advantages of the present invention not mentioned can be understood through the following description, and can be more clearly understood through the embodiments of the present invention. In addition, it can be easily understood that the purpose and advantages of the present invention can be achieved by the means and combinations thereof in the claims.

[0033] Means of solving the problem

[0034] According to one aspect of the present invention for solving the above technical problems, there is provided a positive electrode active material having a bimodal particle size distribution including a first lithium manganese-based oxide and a second lithium manganese-based oxide having different average particle sizes.

[0035] In this article, the first lithium manganese-based oxide may be referred to as a small particle, and the second lithium manganese-based oxide may be referred to as a large particle. The first lithium manganese-based oxide and the second lithium manganese-based oxide constituting the positive electrode active material are oxides formed by solid solution of a phase belonging to a C2 / m space group and a phase belonging to an R-3m space group, respectively.

[0036] Typically, in commercial ternary lithium composite oxides composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA), the phase belonging to the R-3m space group exists as a single phase. However, the lithium-rich lithium manganese-based oxide defined in this article is characterized in that the phase belonging to the C2 / m space group and the phase belonging to the R-3m space group are solid-dissolved or complexed.

[0037] In one embodiment, the first lithium manganese-based oxide and the second lithium manganese-based oxide may be independently a composite oxide including lithium, manganese and a transition metal. The transition metal may include at least one selected from nickel, cobalt and aluminum.

[0038] In the first lithium manganese-based oxide and the second lithium manganese-based oxide constituting the positive electrode active material, the first lithium manganese-based oxide may be selectively substituted with halogen.

[0039] Specifically, at least a portion of oxygen present in the first lithium manganese-based oxide is substituted with halogen.

[0040] Therefore, the first lithium manganese-based oxide may be represented by the following Chemical Formula 1 or Chemical Formula 1-1.

[0041] [Chemical formula 1]

[0042] Li(Li a M1 x M2 y ) 2-b X b

[0043] (wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, M2 and M1 are not repeated, X is a halogen that can replace at least a part of the oxygen present in the above-mentioned lithium manganese-based oxide, and 0 <a≤0.7、0<b≤0.1、0<x≤1、0≤y<1、0<x+y≤1)。

[0044] [Chemical formula 1-1]

[0045] rLi2MnO 3-b" X' b" ·(1 - r)Li a' M1 x' M2 y' O 2-b' X b'

[0046] (wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge, and Nd, M2 does not overlap with M1, X and X' are each independently a halogen capable of substituting at least a part of the oxygen present in the above lithium manganese-based oxide, 0 < r ≤ 0.7, 0 < a' ≤ 1, 0 ≤ b' ≤ 0.1, 0 ≤ b" ≤ 0.1, 0 < x' ≤ 1, 0 ≤ y' < 1, 0 < x' + y' ≤ 1, and b' and b" are not both 0).

[0047] On the other hand, the above second lithium manganese-based oxide can be represented by the following Chemical Formula 2.

[0048] [Chemical Formula 2]

[0049] rLi2MnO3·(1 - r)Li a' M1 x' M2 y' O2

[0050] (wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge, and Nd, M2 does not overlap with M1, 0 < r ≤ 0.7, 0 < a' ≤ 1, 0 < x' ≤ 1, 0 ≤ y' < 1, 0 < x' + y' ≤ 1).

[0051] In one embodiment, a barrier layer is present on the surfaces of the above first lithium manganese-based oxide and the above second lithium manganese-based oxide. The above barrier layer can inhibit or mitigate the dissolution of transition metals from the above first lithium manganese-based oxide and the above second lithium manganese-based oxide.

[0052] The above barrier layer can include an oxide containing at least one element selected from B, Si, P, and Ge.

[0053] Moreover, according to another aspect of the present invention, a positive electrode including the above positive electrode active material is provided.

[0054] According to still another aspect of the present invention, there is provided a lithium secondary battery using the positive electrode.

[0055] Effects of the Invention

[0056] According to the present invention, the limitations of existing lithium-rich lithium manganese-based oxides which are still inferior in electrochemical performance and / or stability compared with commercial ternary lithium composite oxides composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) can be improved.

[0057] Specifically, according to the present invention, the low unit volume energy density of the lithium-rich lithium manganese-based oxide can be improved by preparing the above-mentioned lithium manganese-based oxide by dividing it into small particles and large particles and providing a bimodal positive electrode active material as a mixture of small particles and large particles.

[0058] Furthermore, according to the present invention, by covering the surfaces of small particles and large particles constituting the positive electrode active material having a bimodal particle size distribution with a barrier layer, elution of transition metals from the small particles and large particles can be suppressed or reduced.

[0059] By suppressing or reducing the elution of the transition metal from the small particles and the large particles, it is possible to prevent the transition metal eluted to the surfaces of the small particles and the large particles from reacting with the electrolyte to form impurities.

[0060] The transition metal dissolved from the above-mentioned small particles and the above-mentioned large particles and / or the impurities formed by the reaction of the dissolved transition metal with the electrolyte may move to the negative electrode with the electrolyte as the medium, and the above-mentioned impurities may be deposited on the surface of the negative electrode, resulting in a sharp increase in the negative electrode resistance. Therefore, as described in the present invention, it is necessary to limit the unintentional movement of transition metals in lithium secondary batteries.

[0061] That is, according to the present invention, by forming a barrier layer on the surface of small particles and large particles, it is possible to prevent impurities from being deposited on the positive electrode and / or negative electrode due to transition metals dissolved from the above-mentioned lithium manganese-based oxide to accelerate the life degradation of the lithium secondary battery.

[0062] In addition, the barrier layer can be used as a physical barrier between small particles and large particles and the electrolyte. In particular, OLO such as the lithium manganese-based oxide has the advantage of showing high capacity under high voltage working environment. At this time, the higher the working voltage, the higher the possibility of side reactions between the lithium manganese-based oxide and the electrolyte. Considering this, it is important to reduce the side reactions between the lithium manganese-based oxide and the electrolyte.

[0063] Therefore, by forming a barrier layer on at least a portion of the surface of the small particles and the large particles, the side reaction between the lithium manganese-based oxide and the electrolyte is reduced, thereby improving the stability and life of the lithium secondary battery using the bimodal positive electrode active material defined herein. In particular, the positive electrode active material with suppressed side reactions to the electrolyte can enable the lithium secondary battery to be driven at a higher voltage.

[0064] In addition, according to the present invention, by inducing the selective growth of the above-mentioned small particles in the positive electrode active material having a bimodal particle size distribution, there is a possibility that side reactions caused by the high specific surface area of ​​the small particles relative to the large particles can be reduced.

[0065] In addition to the above-described effects, specific effects of the present invention will be described while explaining specific details for implementing the present invention. DETAILED DESCRIPTION

[0066] Specific terms are defined herein for ease of understanding. Unless specifically defined herein, scientific terms and technical terms used herein should have the meanings commonly understood by those skilled in the art. In addition, it should be understood that as used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form, and vice versa.

[0067] Hereinafter, a positive electrode active material including a lithium-rich lithium manganese-based oxide and a lithium secondary battery including the positive electrode active material according to the present invention will be described in more detail.

[0068] Positive active material

[0069] According to one aspect of the present invention, there is provided a positive electrode active material including a lithium manganese-based oxide in which a phase belonging to a C2 / m space group and a phase belonging to an R-3m space group are solid-dissolved.

[0070] The phase belonging to the C2 / m space group and the phase belonging to the R-3m space group can be distinguished not only by the composition of each phase, but also by the characteristic peaks of each phase during XRD analysis. For example, the characteristic peak of the phase belonging to the C2 / m space group may appear in the region of 2θ=20.8±1°, and the characteristic peak of the phase belonging to the R-3m space group may appear in the region of 2θ=18.6±1°.

[0071] The lithium manganese-based oxide is a composite oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R-3m space group are solid-dissolved, and the phase belonging to the C2 / m space group and the phase belonging to the R-3m space group coexist in the lithium manganese-based oxide. In addition, the lithium manganese-based oxide is different from a composite oxide having a spinel crystal structure belonging to the Fd-3m space group (for example, LiMn2O4 or an oxide having a composition similar thereto).

[0072] Based on the average particle size, the lithium manganese-based oxide can be divided into a first lithium manganese-based oxide as a small particle and a second lithium manganese-based oxide as a large particle. The terms "small particles" and "large particles" as used herein are relative concepts, and a group of particles having an average particle size smaller than the average particle size of the second lithium manganese-based oxide can be defined as small particles, and a group of particles having an average particle size larger than the average particle size of the first lithium manganese-based oxide can be defined as large particles. In addition, as described later, small particles and large particles can be defined by the range of average particle sizes, respectively.

[0073] Therefore, the positive electrode active material defined herein is a positive electrode active material having a bimodal particle size distribution due to the inclusion of the first lithium manganese-based oxide as small particles and the second lithium manganese-based oxide as large particles.

[0074] Bimodal particle size distribution refers to the distribution of two peaks with different particle sizes when the above-mentioned positive electrode active material is subjected to laser diffraction particle size analysis. Therefore, in the volume cumulative particle size distribution diagram, the lithium manganese-based oxide showing a peak at a relatively small particle size is a small particle (the first lithium manganese-based oxide), and the lithium manganese-based oxide showing a peak at a relatively large particle size is a large particle (the second lithium manganese-based oxide).

[0075] Hereinafter, unless otherwise defined, the above-mentioned lithium manganese-based oxide may be understood to refer to the above-mentioned first lithium manganese-based oxide and the above-mentioned second lithium manganese-based oxide, both of which are included.

[0076] The lithium manganese-based oxide contains at least lithium, manganese and a transition metal. The transition metal may include at least one selected from nickel, cobalt and aluminum. In addition, the lithium manganese-based oxide may include lithium, nickel and manganese, and may optionally further include a transition metal other than nickel.

[0077] The content of lithium in the above-mentioned lithium manganese-based oxide is greater than the sum of the contents of other transition metals (generally, the molar ratio of lithium to all metal elements except lithium in the lithium manganese-based oxide (lithium / metal molar ratio (Li / Metal molar ratio) is greater than 1), so it is also called lithium-rich layered oxide (overlithiated layered oxide; OLO).

[0078] In addition, since the content of manganese in the lithium manganese-based oxide is greater than the content of other transition metals, the lithium manganese-based oxide is also called a layered oxide with excess lithium and manganese.

[0079] Generally speaking, considering that the manganese content in the total metal elements other than lithium in the commercial nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) ternary lithium composite oxide is less than 20 mol%, the above-mentioned lithium manganese-based oxide has a relatively high ratio of manganese in the total metal elements (for example, more than 50 mol%, more than 52 mol%, more than 53 mol% or more than 55 mol%) compared with the commercial ternary lithium composite oxide.

[0080] Furthermore, considering that the content of nickel in the total metal elements other than lithium in the commercialized nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) ternary lithium composite oxide is more than 60 mol% (more than 80 mol% in the case of high-nickel lithium composite oxides), the above-mentioned lithium manganese-based oxide has a relatively low ratio of nickel in the total metal elements (for example, less than 50 mol%, less than 48 mol%, less than 46 mol%, less than 45 mol%, less than 44 mol%, less than 42 mol% or less than 40 mol%) compared with the commercialized ternary lithium composite oxide.

[0081] There is also a difference that the lithium / metal molar ratio measured from the lithium manganese-based oxide defined herein is greater than the lithium / metal molar ratio of a ternary lithium composite oxide such as nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA). For example, the lithium / metal molar ratio of a ternary lithium composite oxide such as nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA) appears to be close to 1. On the other hand, the lithium / metal molar ratio of the lithium manganese-based oxide defined herein is greater than 1, preferably 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5.

[0082] Therefore, herein, the lithium manganese-based oxide may be defined as a composite oxide having a manganese content of 50 mol% or more in the total metal elements other than lithium, or may be defined as a composite oxide having a manganese content of 50 mol% or more and a nickel content of less than 50 mol% in the total metal elements other than lithium.

[0083] In addition, the molar ratio of lithium to all metal elements other than lithium in the lithium manganese-based oxide herein is greater than 1, or is 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5, and it is defined as a composite oxide in which the manganese content in all metal elements other than lithium is 50 mol% or more, or a composite oxide in which the molar ratio of lithium to all metal elements other than lithium is greater than 1, or is 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5, the manganese content in all metal elements other than lithium is 50 mol% or more, and the nickel content is less than 50 mol%.

[0084] Despite the above-mentioned difference in composition, the above-mentioned lithium manganese-based oxide can also be used as a composite metal oxide capable of intercalating / deintercalating lithium ions.

[0085] The lithium composite oxide contained in the positive electrode active material as defined herein may be present as particles including at least one primary particle.

[0086] When the lithium manganese-based oxide exists as a single primary particle, the lithium composite oxide may be referred to as a single particle. On the other hand, when the lithium manganese-based oxide exists as an aggregate formed by agglomerating a plurality of primary particles, the lithium composite oxide may be referred to as a secondary particle.

[0087] The positive electrode active material may include at least one selected from the group consisting of a lithium manganese-based oxide present as a single particle and a lithium manganese-based oxide present as a secondary particle formed by agglomerating a plurality of primary particles.

[0088] The primary particles constituting the above-mentioned lithium manganese-based oxide may have a rod (rod) shape, an elliptical shape and / or an irregular shape. In addition, unless specifically designed during the manufacturing process, primary particles of various shapes exist in the same positive electrode active material. In addition, the above-mentioned primary particles refer to particle units that do not appear to have grain boundaries when observed with a scanning electron microscope at a magnification of 5000 to 20000 times.

[0089] The average particle size of the primary particles constituting the lithium manganese-based oxide defined herein may be 0.05 μm to 5 μm, 0.05 μm to 1.0 μm, 0.1 μm to 1.0 μm, or 0.25 μm to 0.75 μm. At this time, as the average particle size of the primary particles, the average value of the length in the major axis direction and the length in the minor axis direction of the primary particles ([major axis length + minor axis length] / 2) may be used.

[0090] When the average particle size of the primary particles is less than 0.05 μm, the specific surface area of ​​the lithium manganese-based oxide (secondary particles) composed of the primary particles is large. In this case, the possibility of causing a side reaction between the lithium manganese-based oxide and the electrolyte during storage or operation of the lithium secondary battery increases.

[0091] On the other hand, when the average particle size of the primary particles is greater than 5 μm, the growth of the primary particles is excessively induced, so the diffusion path of lithium ions in the primary particles also becomes longer. When the diffusion path of lithium ions in the primary particles is too long, the mobility of lithium ions in the primary particles and the diffusivity of lithium ions through the primary particles are reduced, which becomes a cause of increasing the resistance of the lithium composite oxide (secondary particles) composed of the primary particles.

[0092] By setting the difference between the average particle size of the second lithium manganese-based oxide and the average particle size of the first lithium manganese-based oxide to be 3 μm or more, preferably 4 μm or more, the energy density per unit volume of the bimodal positive electrode active material can be increased.

[0093] The main peak of the volume-based particle size distribution curve (x-axis: particle size (μm), Y-axis: volume %) of the first lithium manganese-based oxide may be between 1 μm and 8 μm, preferably, between 2 μm and 7 μm. In addition, the average particle size calculated as the average value of the length in the major axis direction and the length in the minor axis direction of the first lithium manganese-based oxide ([major axis length + minor axis length] / 2) may be 2 μm to 6 μm.

[0094] The main peak of the volume-based particle size distribution curve (x-axis: particle size (μm), Y-axis: volume %) of the second lithium manganese-based oxide may be between 6 μm and 24 μm, preferably, between 8 μm and 22 μm. In addition, the average particle size calculated as the average value of the length in the major axis direction and the length in the minor axis direction of the second lithium manganese-based oxide ([major axis length + minor axis length] / 2) may be 7 μm to 14 μm.

[0095] Furthermore, in order to optimize the energy density per unit volume of the bimodal positive electrode active material, the weight ratio of the first lithium manganese-based oxide to the second lithium manganese-based oxide in the positive electrode active material is preferably 10:90 to 80:20, 20:80 to 70:30 or 30:70 to 60:40.

[0096] The first lithium manganese-based oxide may exist in a form of filling gaps between the second lithium manganese-based oxides, or may be attached to the surface of the second lithium manganese-based oxide, or may exist in a form of agglomeration of the first lithium manganese-based oxides.

[0097] When the ratio of the first lithium manganese-based oxide to the second lithium manganese-based oxide in the positive electrode active material is too small, it may be difficult to sufficiently fill the voids formed by the second lithium manganese-based oxide with the first lithium manganese-based oxide.

[0098] On the other hand, when the ratio of the first lithium manganese-based oxide to the second lithium manganese-based oxide in the positive electrode active material is too large, the energy density per unit volume of the positive electrode active material may decrease.

[0099] The average particle size of the first lithium manganese-based oxide and the second lithium manganese-based oxide may vary depending on the number of the primary particles constituting the secondary particles. The average particle size (D50) of the first lithium manganese-based oxide and the second lithium manganese-based oxide may be measured using a laser diffraction method. For example, after the first lithium manganese-based oxide and the second lithium manganese-based oxide are dispersed in a dispersion medium, they are introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), irradiated with an ultrasonic wave of about 28 kHz at a power of 60 W, and then a volume cumulative particle size distribution diagram is obtained, and the particle size equivalent to 50% of the volume cumulative amount is obtained to achieve measurement.

[0100] In addition, the BET specific surface area of ​​the first lithium manganese-based oxide may be 1.0 m 2 / g to 1.8m 2 / g, 1.0m 2 / g to 1.7m 2 / g, 1.2m 2 / g to 1.7m 2 / g or 1.3m 2 / g to 1.6m 2 / g. The BET specific surface area of ​​the second lithium manganese-based oxide may be 1.5 m 2 / g to 2.3m 2 / g, 1.5m 2 / g to 2.1m 2 / g, 1.5m 2 / g to 2.0m 2 / g or 1.6m 2 / g to 1.9m 2 The range of the BET specific surface area of ​​the first lithium manganese-based oxide and the range of the BET specific surface area of ​​the second lithium manganese-based oxide may be determined by any combination of the above numerical ranges.

[0101] In addition, the absolute value of the difference (ΔBET) between the BET specific surface area of ​​the first lithium manganese-based oxide and the second lithium manganese-based oxide may be 0.8 m 2 / g or less, 0.6m 2 / g or less, 0.5m 2 / g or less or 0.4m 2 / g or less.

[0102] The first lithium manganese-based oxide as a small particle has more voids in the particles and / or between the particles than the second lithium manganese-based oxide as a large particle, and has a high specific surface area compared to the particle size, so the possibility of side reactions with the electrolyte is high. Therefore, when the selective growth of the primary particles constituting the first lithium manganese-based oxide is induced by replacing at least a part of the oxygen present in the first lithium manganese-based oxide with a halogen (e.g., fluorine), the specific surface area of ​​the first lithium manganese-based oxide can be reduced. In addition, as described above, the first lithium manganese-based oxide as a small particle has more voids in the particles and / or between the particles than the second lithium manganese-based oxide as a large particle, so the growth effect of the primary particles (the porosity in the particles decreases when the primary particles grow) caused by replacing at least a part of the oxygen present in the first lithium manganese-based oxide with a halogen (e.g., fluorine) may be significant.

[0103] Unless otherwise defined, the term "surface of the primary particle" as used herein refers to the outer surface of the primary particle exposed to the outside. Similarly, the term "surface of the secondary particle" as used herein refers to the outer surface of the secondary particle exposed to the outside. In this case, the "surface of the secondary particle" formed by the agglomeration of multiple primary particles is equivalent to the exposed surface of the primary particle existing on the surface of the secondary particle.

[0104] In addition, unless otherwise defined, the term "surface portion of a particle" as used herein refers to a region relatively close to the "outermost surface" of a particle, and "center portion of a particle" refers to a region relatively close to the "exact center" of a particle compared to the above-mentioned "surface portion". Therefore, the "surface portion of a primary particle" refers to a region relatively close to the "outermost surface" of the above-mentioned primary particle, and the "center portion of a primary particle" refers to a region relatively close to the "exact center" of the above-mentioned primary particle compared to the above-mentioned "surface portion". Similarly, the "surface portion of a secondary particle" refers to a region relatively close to the "outermost surface" of the above-mentioned secondary particle, and the "center portion of a secondary particle" refers to a region relatively close to the "exact center" of the above-mentioned secondary particle compared to the above-mentioned "surface portion".

[0105] At this time, a region other than the “surface portion of the particle” within any particle can be defined as the “center portion of the particle”.

[0106] For example, when the radius of the primary particle is r, the region at a distance of 0r to 0.5r from the surface of the primary particle can be defined as the surface portion of the primary particle, and the region at a distance of 0r to 0.5r from the exact center of the primary particle can be defined as the central portion of the primary particle. If the radius of the primary particle is 0.5 μm, the surface portion of the primary particle can be defined as the region at a distance of 0 μm to 0.25 μm from the surface of the primary particle, and the central portion of the primary particle can be defined as the region at a distance of 0 μm to 0.25 μm from the exact center of the primary particle.

[0107] In addition, as needed, when the radius of the above-mentioned primary particle is r, the area with a distance of 0r to 0.1r or 0r to 0.2r from the surface of the above-mentioned primary particle can be defined as the surface part of the above-mentioned primary particle, and the area with a distance of 0r to 0.2r or 0r to 0.5r from the exact center of the above-mentioned primary particle can be defined as the central part of the above-mentioned primary particle.

[0108] Similarly, when the radius of the secondary particle is r, the region at a distance of 0r to 0.5r from the surface of the secondary particle can be defined as the surface portion of the secondary particle, and the region at a distance of 0r to 0.5r from the exact center of the secondary particle can be defined as the central portion of the secondary particle. If the radius of the secondary particle is 2.0 μm, the surface portion of the secondary particle can be defined as the region at a distance of 0 μm to 1.0 μm from the surface of the secondary particle, and the central portion of the secondary particle can be defined as the region at a distance of 0 μm to 1.0 μm from the exact center of the secondary particle.

[0109] In addition, as needed, when the radius of the above-mentioned secondary particle is r, the region with a distance of 0r to 0.1r or 0r to 0.2r from the surface of the above-mentioned secondary particle can be defined as the surface portion of the above-mentioned secondary particle, and the region with a distance of 0r to 0.2r or 0r to 0.5r from the exact center of the above-mentioned secondary particle can be defined as the central portion of the above-mentioned secondary particle.

[0110] In one embodiment, in the first lithium manganese-based oxide and the second lithium manganese-based oxide constituting the positive electrode active material, the first lithium manganese-based oxide may be selectively substituted with halogen. The selective halogen substitution of the first lithium manganese-based oxide means that the first lithium manganese-based oxide in the positive electrode active material is substituted with halogen, while the second lithium manganese-based oxide is not substituted with halogen.

[0111] Specifically, at least a portion of oxygen present in the first lithium manganese-based oxide is substituted with halogen.

[0112] Therefore, the above-mentioned first lithium manganese-based oxide can be represented by the following Chemical Formula 1 or Chemical Formula 1-1. Additionally, the composition represented by the following Chemical Formula 1 or Chemical Formula 1-1 can represent the average composition reflecting the composition of the barrier layer present on the surface of the above-mentioned first lithium manganese-based oxide.

[0113] [Chemical Formula 1]

[0114] Li(Li a M1 x M2 y )O 2-b X b

[0115] Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge, and Nd, M2 does not overlap with M1, X is a halogen capable of substituting at least a part of the oxygen present in the above-mentioned lithium manganese-based oxide, and 0 < a ≤ 0.7, 0 < b ≤ 0.1, 0 < x ≤ 1, 0 ≤ y < 1, 0 < x + y ≤ 1.

[0116] [Chemical Formula 1-1]

[0117] rLi2MnO 3-b" X' b" ·(1 - r)Li a' M1 x' M2 y' O 2-b' X b'

[0118] Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge, and Nd, M2 does not overlap with M1, X and X' are each independently a halogen capable of substituting at least a part of the oxygen present in the above-mentioned lithium manganese-based oxide, 0 < r ≤ 0.7, 0 < a' ≤ 1, 0 ≤ b' ≤ 0.1, 0 ≤ b" ≤ 0.1, 0 < x' ≤ 1, 0 ≤ y' < 1, 0 < x' + y' ≤ 1, and b' and b" are not both 0.

[0119] X and X' are independently halogens that can replace at least a portion of the oxygen present in the lithium manganese-based oxide. As the types of halogens that can be used as X and X', F, Cl, Br and / or I can be used with reference to the periodic table, and preferably F can be used.

[0120] As described above, when halogen is doped when inducing the growth of the primary particles constituting the first lithium manganese-based oxide, preferably, at least a part of oxygen present in the first lithium manganese-based oxide may be substituted with halogen.

[0121] In order to induce the particle growth of the above-mentioned primary particles constituting the above-mentioned first lithium manganese-based oxide, when an over-calcination method of heat treatment at a relatively high temperature without doping halogen particles is used, the growth of the above-mentioned primary particles can be achieved, but the crystal structure of the above-mentioned primary particles is damaged, so the above-mentioned first lithium manganese-based oxide may deteriorate prematurely.

[0122] In addition, in the case of the over-calcination method, the growth of the primary particles shows non-directionality, but when halogen is doped during the growth of the primary particles, the growth of the primary particles shows partial directionality, thereby reducing the reduction in the diffusivity of lithium ions due to the growth of the primary particles. In particular, fluorine is preferably used as an anion dopant to grow the primary particles in a range that reduces the reduction in the diffusivity of lithium ions through the primary particles, in order to induce crystal growth or grain growth of the primary particles in a selective direction.

[0123] In order to dope fluorine in the above-mentioned primary particles, at least one anion dopant selected from LiF, MgF2, HF, F2, XeF2, TbF4, CeF4, CoF3, AgF2, MoF3, AgF, CuF2, FeF3, Cu F, VF3, CrF3, ZrF4, BaF2, CaF2, AlF3, NH4F, CeF3 and CsF can be used. Preferably, at least one anion dopant selected from LiF and MgF2 can be used.

[0124] In the above Chemical Formula 1, when M1 is Ni, M2 may include Mn, and when M1 is Mn, M2 may include Ni. In addition, when M1 is Ni and Mn, M2 may not exist, or, if present, may be an element other than Ni and Mn.

[0125] That is, when M1 is Ni, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd (preferably at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably at least one selected from Co, P, B, Si, Ti, Zr and W, and even more preferably at least one selected from P, B and Si) and Mn.

[0126] When M1 is Mn, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd (preferably at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably at least one selected from Co, P, B, Si, Ti, Zr and W, even more preferably at least one selected from P, B and Si) and Ni.

[0127] When M1 is Ni and Mn, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, preferably, may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably, may include at least one selected from Co, P, B, Si, Ti, Zr and W, even more preferably, may include at least one selected from P, B and Si.

[0128] On the other hand, the second lithium manganese-based oxide may be represented by Chemical Formula 2 below.

[0129] [Chemical formula 2]

[0130] rLi2MnO3·(1-r)Li a' M1 x' M2 y' O2

[0131] Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, M2 and M1 are not repeated, and 0 <r≤0.7、0<a'≤1、0<x'≤1、0≤y'<1、0<x'+y'≤1。

[0132] Since the above-mentioned second lithium manganese-based oxide as large particles has fewer voids within and / or between particles than the above-mentioned first lithium manganese-based oxide as small particles, it may be difficult to induce the growth of primary particles by replacing at least a portion of the oxygen present in the above-mentioned second lithium manganese-based oxide with halogen (e.g., fluorine).

[0133] In addition, unlike the first lithium manganese-based oxide, when the second lithium manganese-based oxide is doped with halogen (e.g., fluorine), the electrochemical performance of the positive electrode active material having a bimodal particle size distribution defined herein may be reduced (e.g., capacity and efficiency are reduced).

[0134] Likewise, in the above Chemical Formula 2, when M1 is Ni, M2 may include Mn, and when M1 is Mn, M2 may include Ni. In addition, when M1 is Ni and Mn, M2 may not exist, or, if present, may be an element other than Ni and Mn.

[0135] That is, when M1 is Ni, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd (preferably at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably at least one selected from Co, P, B, Si, Ti, Zr and W, and even more preferably at least one selected from P, B and Si) and Mn.

[0136] When M1 is Mn, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd (preferably at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably at least one selected from Co, P, B, Si, Ti, Zr and W, even more preferably at least one selected from P, B and Si) and Ni.

[0137] When M1 is Ni and Mn, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, preferably, may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably, may include at least one selected from Co, P, B, Si, Ti, Zr and W, even more preferably, may include at least one selected from P, B and Si.

[0138] The lithium manganese-based oxide represented by the above chemical formula 1, the above chemical formula 1-1 and the above chemical formula 2 may optionally include cobalt. In addition, when the above lithium manganese-based oxide includes cobalt, the molar number of the above cobalt relative to the molar number of the entire metal element in the above lithium manganese-based oxide may be 20% or less, preferably, 15% or less, and more preferably, 10% or less. In another case, the lithium manganese-based oxide represented by the above chemical formula 1 may have a cobalt-free composition that does not contain cobalt.

[0139] The lithium / metal molar ratio measured from the lithium manganese-based oxide represented by the above Chemical Formula 1, the above Chemical Formula 1-1 and the above Chemical Formula 2 may be greater than 1, and preferably, may be 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5. Only when the lithium / metal molar ratio measured from the above lithium manganese-based oxide is at least greater than 1, a lithium-rich lithium manganese-based oxide can be formed.

[0140] In addition, in order to make the above-mentioned lithium manganese-based oxide appropriately form a solid solution formed by solid dissolution or complexation of a phase belonging to the C2 / m space group and a phase belonging to the R-3m space group, and at the same time exert high capacity under a high voltage working environment, the lithium / metal molar ratio of the above-mentioned lithium manganese-based oxide is preferably 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5.

[0141] In addition, in order to appropriately form a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R-3m space group, the manganese content in the entire metal elements other than lithium present in the above-mentioned lithium manganese-based oxide is preferably 50 mol% or more.

[0142] In order to make the above-mentioned lithium manganese-based oxide have OLO characteristics showing high capacity under a high voltage operating environment, the content of manganese in the total metal elements other than lithium present in the above-mentioned lithium manganese-based oxide may be 50 mol% or more and less than 80 mol%, 51 mol% or more and less than 80 mol%, 52 mol% or more and less than 80 mol%, 53 mol% or more and less than 80 mol%, 54 mol% or more and less than 80 mol%, 55 mol% or more and less than 80 mol%, 50 mol% or more and 75 mol%, 51 mol% or more and 75 mol%, 52 mol% or more and 75 mol%, 53 mol% or more and 75 mol%, 54 mol% or more and 75 mol%, or 55 mol% to 75 mol%.

[0143] When the manganese content in the above-mentioned lithium manganese-based oxide exceeds 80 mol%, a phase change may occur during the formation and / or operation of the lithium secondary battery due to the movement of the transition metal (especially manganese) in the above-mentioned lithium manganese-based oxide. The above-mentioned phase change forms a spinel phase, and the above-mentioned spinel acting as an impurity in the above-mentioned lithium manganese-based oxide can cause a decrease in charge / discharge capacity or voltage decay when the lithium secondary battery is cycled. In addition, when the manganese content in the above-mentioned lithium manganese-based oxide exceeds 80 mol%, the above-mentioned lithium manganese-based oxide may exhibit the characteristics of a composite oxide (for example, LiMn2O4 or an oxide having a similar composition thereto) having a spinel crystal structure belonging to the Fd-3m space group.

[0144] In order to properly form a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R-3m space group, the content of nickel in the entire metal elements other than lithium present in the above-mentioned lithium manganese-based oxide can be less than 50 mol%, less than 48 mol%, less than 46 mol%, less than 45 mol%, less than 44 mol%, less than 42 mol% or less than 40 mol%.

[0145] When the nickel content in the above-mentioned lithium manganese-based oxide is above 50 mol%, it is difficult to fully form the C2 / m phase, or the phase belonging to the C2 / m space group and the phase belonging to the R-3m space group may not form a sufficient solid solution, resulting in phase separation during the formation and / or operation of the lithium secondary battery.

[0146] Generally, in a commercially available ternary lithium composite oxide composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA), a phase belonging to the R-3m space group exists as a single-phase.

[0147] On the other hand, the lithium-rich lithium manganese-based oxide represented by the above chemical formula 1, the above chemical formula 1-1 and the above chemical formula 2 is composed of rLi2MnO 3-b" X' b" or rLi2MnO3 and an oxide of a phase belonging to the C2 / m space group (hereinafter referred to as "C2 / m phase") and (1-r)Li a' M1 x' M2 y' O 2-b' X b' or (1-r)Li a' M1 x' M2 y' A composite oxide formed by solid solution or complexation of an oxide belonging to a phase of the R-3m space group represented by O2 (hereinafter referred to as "R-3m phase") exists. For example, the lithium manganese-based oxide may exist in a state where an oxide of the C2 / m phase and an oxide of the R-3m phase form a solid solution.

[0148] In this case, a composite oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R-3m space group are simply physically and / or chemically bonded or attached does not correspond to the solid solution defined herein.

[0149] For example, a metal oxide having a phase belonging to the C2 / m space group whose surface is coated with a metal oxide belonging to the R-3m space group by mixing a metal oxide having a phase belonging to the C2 / m space group and a metal oxide having a phase belonging to the R-3m space group does not correspond to the solid solution defined in this article.

[0150] In the lithium manganese-based oxide, when r exceeds 0.7, the ratio of the oxide of the C2 / m phase in the lithium manganese-based oxide increases excessively, which may lead to an increase in the irreversible capacity and resistance of the positive electrode active material, thereby reducing the discharge capacity. That is, in order to fully activate the C2 / m phase oxide with relatively high resistance in the lithium manganese-based oxide to improve the surface dynamics, the R-3m phase oxide is preferably present at a predetermined ratio or more.

[0151] In one embodiment, a barrier layer exists on the surface of the first lithium manganese-based oxide and the second lithium manganese-based oxide. The barrier layer can inhibit or reduce the dissolution of transition metals from the first lithium manganese-based oxide and the second lithium manganese-based oxide. In addition, the barrier layer can improve the charge transfer and / or diffusivity (i.e., surface dynamic performance) of lithium ions while preventing side reactions with the electrolyte by covering the surface of the first lithium manganese-based oxide and the second lithium manganese-based oxide.

[0152] The barrier layer may exist in the form of islands covering at least a portion of the surface of the first lithium manganese-based oxide and the second lithium manganese-based oxide. Even if the barrier layer exists in the form of islands, the dissolution of transition metals can be suppressed or reduced by the area covered by the barrier layer.

[0153] In addition, when the first lithium manganese-based oxide and the second lithium manganese-based oxide exist as secondary particles, the barrier layer may exist in a state of diffusion from the surface of the secondary particles to the center of the secondary particles along the grain boundaries between the primary particles. Preferably, the main element constituting the barrier layer (for example, at least one selected from boron (B), silicon (Si), phosphorus (P) and germanium (Ge), preferably boron (B)) may form a concentration gradient that decreases from the surface (outermost layer) of the secondary particles to the inside of the secondary particles.

[0154] By forming the barrier layer in a gradient from the surface portion of the secondary particle toward the center portion of the secondary particle, it is possible to effectively suppress or alleviate the elution of transition metal mainly from the surface portion of the secondary particle.

[0155] Therefore, when the main elements constituting the above-mentioned barrier layer (for example, boron (B), silicon (Si), phosphorus (P) and germanium (Ge)) are referred to as barrier layer elements, the atomic ratio of the barrier layer elements calculated based on the number of atoms of nickel, manganese and the barrier layer elements present inside the above-mentioned secondary particles may be smaller than the atomic ratio of the barrier layer elements calculated based on the number of atoms of nickel, manganese and the barrier layer elements present on the surface of the above-mentioned secondary particles. In addition, the atomic ratio of the barrier layer elements calculated based on the total number of atoms of nickel, manganese and the barrier layer elements constituting the above-mentioned secondary particles may be smaller than the atomic ratio of the barrier layer elements calculated based on the number of atoms of nickel, manganese and the barrier layer elements present on the surface (outermost layer) of the above-mentioned secondary particles.

[0156] In some embodiments, a portion of the main element constituting the above-mentioned barrier layer (for example, at least one selected from boron (B), silicon (Si), phosphorus (P) and germanium (Ge), preferably boron (B)) may be present on the surface of the above-mentioned primary particle at a higher concentration than in the interior of the above-mentioned primary particle.

[0157] Therefore, when the main elements constituting the barrier layer (e.g., boron (B), silicon (Si), phosphorus (P), and germanium (Ge)) are referred to as barrier layer elements, the atomic ratio of the barrier layer elements calculated based on the atomic number of nickel, manganese, and the barrier layer elements present in the primary particle may be smaller than the atomic ratio of the barrier layer elements calculated based on the atomic number of nickel, manganese, and the barrier layer elements present on the surface (outermost layer) of the primary particle. In addition, the atomic ratio of the barrier layer elements calculated based on the total atomic number of nickel, manganese, and the barrier layer elements constituting the primary particle may be smaller than the atomic ratio of the barrier layer elements calculated based on the atomic number of nickel, manganese, and the barrier layer elements present on the surface (outermost layer) of the primary particle.

[0158] In addition, the barrier layer may be present on the surface of the first lithium manganese-based oxide and the second lithium manganese-based oxide in the form of a film having a thickness of 1 nm to 300 nm. The barrier layer being present in the form of a film should be distinguished from the oxide constituting the barrier layer being dispersed in the form of individual particles and attached to the surface of the lithium manganese-based oxide.

[0159] When the average film thickness of the barrier layer is less than 1 nm, it may be difficult to fully inhibit the dissolution of transition metals from the first lithium manganese-based oxide and the second lithium manganese-based oxide. On the other hand, when the average film thickness of the barrier layer is greater than 300 nm, the surface dynamic properties or electrical conductivity of the first lithium manganese-based oxide and the second lithium manganese-based oxide may be reduced.

[0160] In addition, as the thickness of the barrier layer present on the surface of the lithium manganese-based oxide becomes thicker, the transition metal can be prevented from dissolving from the lithium manganese-based oxide, thereby improving the short-term life of the lithium secondary battery using the lithium manganese-based oxide as the positive electrode active material. However, on the contrary, if the thickness of the barrier layer becomes too thick (for example, exceeding 300nm), the gas generation in the lithium secondary battery may increase sharply.

[0161] The barrier layer may include an oxide containing at least one element selected from the group consisting of B, Si, P, and Ge.

[0162] For example, the barrier layer may include an oxide represented by Chemical Formula 3 below.

[0163] [Chemical formula 3]

[0164] zLi2O*(1-z)M3 d O e

[0165] Among them, M3 is at least one element selected from B, Si, P, and Ge, and 0 < z ≤ 0.8, 0 < d ≤ 10, 0 < e ≤ 10. Here, d and e represent numbers determined from the stoichiometric ratio according to the valence of M3.

[0166] In addition, preferably, the above barrier layer may include at least one boron-containing compound selected from B2O3, H α B β O γ (0 < α < 10, 0 < β < 10, 0 < γ < 20) and Li α' B β' O γ' (0 < α' < 10, 0 < β' < 10, 0 < γ' < 20). Here, α, β, γ, α', β', and γ' represent numbers determined from the stoichiometric ratio. Non-limiting examples of the above boron-containing oxides include H3BO3, B2O3, Li2O - B2O3, Li3BO3, Li2B4O7, Li2B2O7, Li2B8O 13 etc.

[0167] Lithium secondary battery

[0168] According to another aspect of the present invention, a positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the above positive electrode current collector can be provided. Among them, the above positive electrode active material layer may include the lithium manganese-based oxide according to various embodiments of the present invention as the positive electrode active material.

[0169] Therefore, specific descriptions of the lithium manganese-based oxide will be omitted. Hereinafter, only the remaining components not described above will be described. In addition, for convenience hereinafter, the above lithium manganese-based oxide is referred to as the positive electrode active material.

[0170] The above positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or those obtained by surface-treating the surface of aluminum or stainless steel with carbon, nickel, titanium, silver, etc. can be used. And the above positive electrode current collector usually may have a thickness of 3 μm to 500 μm, and fine irregularities may also be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. For example, it can be used in various forms such as a thin film, sheet, foil, net, porous body, foam, non-woven body, etc.

[0171] The above positive electrode active material layer can be prepared by coating a positive electrode paste composition containing the above positive electrode active material, a conductive material, and optionally a binder on the above positive electrode current collector.

[0172] In this case, the content of the positive electrode active material can be 80 wt % to 99 wt %, more specifically 85 wt % to 98.5 wt % relative to the total weight of the positive electrode active material layer. When the positive electrode active material is included in the above content range, excellent capacity performance can be shown, but it is not limited thereto.

[0173] The above-mentioned conductive materials are used to impart conductivity to the electrode. In the battery formed, as long as they do not cause chemical changes and have electronic conductivity, they can be used without limitation. As specific examples, graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and one of them or a mixture of two or more thereof can be used. The above-mentioned conductive material may be included in an amount of 0.1% to 15% by weight relative to the total weight of the positive electrode active material layer.

[0174] The above-mentioned binder plays a role in improving the adhesion between multiple positive electrode active material particles and the bonding force between the positive electrode active material and the collector. As a specific example, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated ethylene propylene diene rubber, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, etc., can be used. One or a mixture of two or more thereof. Relative to the total weight of the positive electrode active material layer, 0.1% to 15% by weight of the above-mentioned binder may be included.

[0175] In addition to using the above-mentioned positive electrode active material, the above-mentioned positive electrode can be prepared according to a common positive electrode preparation method. Specifically, it can be prepared by coating a positive electrode slurry composition on a positive electrode collector and then drying and rolling it. The above-mentioned positive electrode slurry composition is prepared by dissolving or dispersing the above-mentioned positive electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent.

[0176] The above-mentioned solvent may be a solvent commonly used in the art, and examples thereof include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone or water, and a mixture of one or more thereof may be used. Considering the coating thickness and preparation yield of the slurry, the amount of the above-mentioned solvent used is sufficient to dissolve or disperse the above-mentioned positive electrode active material, conductive material and binder and have a viscosity that can show excellent thickness uniformity when applied to prepare the positive electrode.

[0177] Furthermore, in another embodiment, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support, and then laminating a thin film obtained by peeling the support on a positive electrode collector.

[0178] In addition, according to another aspect of the present invention, an electrochemical device comprising the positive electrode described above can be provided. Specifically, the electrochemical device described above can be a battery, a capacitor, etc., and more specifically, can be a lithium secondary battery.

[0179] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and a separation membrane and an electrolyte disposed between the positive electrode and the negative electrode. The positive electrode is the same as the above description, so for convenience, the specific description is omitted, and only the remaining configuration not described above is described below.

[0180] The lithium secondary battery may further include: a battery container for accommodating the electrode assembly of the positive electrode, the negative electrode and the separation membrane; and a sealing member for sealing the battery container.

[0181] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0182] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can usually have a thickness of 3 μm to 500 μm. Similar to the positive electrode current collector, the binding force of the negative electrode active material can be strengthened by forming fine concave and convex on the surface of the collector. For example, it can be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a non-woven body.

[0183] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition including the negative electrode active material and a conductive material and optionally including a binder as required on the negative electrode collector.

[0184] As the negative electrode active material, a compound capable of reversibly inserting and extracting lithium can be used. Specific examples include carbon materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; such as SiO β (0<β<2), SnO2, vanadium oxide, lithium vanadium oxide, metal oxides capable of being doped and dedoped with lithium; or composites containing the above metal compounds and carbon materials such as Si-C composites or Sn-C composites, etc., and one or a mixture of two or more of them can be used. In addition, as the above-mentioned negative electrode active material, a metal lithium film can also be used. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative low-crystalline carbons are soft carbon and hard carbon, and representative high-crystalline carbons are amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite (Kishgraphite), pyrolytic carbon (pyrolytic carbon), mesophase pitch based carbon fiber (mesophase pitch based carbon fiber), mesophase carbon microbeads (meso-carbon microbeads), mesophase pitch (Mesophase pitches) and petroleum or coal tar pitch derived cokes (petroleum or coal tar pitch derived cokes) and other high-temperature sintered carbons.

[0185] The negative electrode active material layer may contain 80 wt % to 99 wt % of the negative electrode active material, based on the total weight of the negative electrode active material layer.

[0186] The binder is a component that helps to bind the conductive material, the active material and the collector. Usually, based on the total weight of the negative electrode active material layer, 0.1 wt % to 10 wt % of the binder can be added. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber, sulfonated ethylene propylene diene rubber, styrene butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.

[0187] The conductive material is a component used to further improve the conductivity of the negative electrode active material. Based on the total weight of the negative electrode active material layer, the conductive material can be added in an amount of 10% by weight or less, preferably 5% by weight or less. There are no particular restrictions on such conductive materials as long as they do not induce chemical changes in the corresponding battery and have conductivity. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. can be used.

[0188] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition on a negative electrode collector and drying it, wherein the negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent, or by casting the negative electrode slurry composition on a separate support and laminating a thin film obtained by peeling off the support on the negative electrode collector.

[0189] On the other hand, in the above-mentioned lithium secondary battery, the separation membrane is used to separate the negative electrode and the positive electrode and provide a mobile channel for lithium ions. As long as the separation membrane commonly used in the lithium secondary battery, it can be used without restriction, especially, preferably, for the ion movement of the electrolyte, the impedance is low and there is excellent electrolyte moisture-containing capacity. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers or their two or more layers of stacked structures. In addition, a common porous non-woven fabric can also be used, for example, a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, in order to ensure heat resistance or mechanical strength, a separation membrane coated with a ceramic component and a polymer substance can also be used, which can be selectively used with a single layer or multilayer structure.

[0190] Furthermore, examples of the electrolyte used in the present invention include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in preparing lithium secondary batteries.

[0191] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0192] As the above-mentioned organic solvent, any organic solvent that can act as a medium for the movement of ions involved in the electrochemical reaction of the battery can be used without limitation. Specifically, as the above-mentioned organic solvent, ester solvents such as methylacetate, ethylacetate, γ-butyrolactone, and ε-caprolactone; ether solvents such as dibutyl ether and tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methylethyl carbonate (MEC), ethylmethyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (EPC), etc. can be used. carbonate, PC) and other carbonate solvents; alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (r is a straight-chain, branched or cyclic hydrocarbon group with 2 to 20 carbon atoms, which may contain a double-bonded aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane, etc. Among them, carbonate solvents are preferred, and more preferably, a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate) with high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery, and low-viscosity linear carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.). In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, excellent electrolyte performance can be shown.

[0193] The above-mentioned lithium salt can be used without limitation as a compound that can provide lithium ions used in a lithium secondary battery. Specifically, the above-mentioned lithium salt can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2, etc. Preferably, the concentration of the above-mentioned lithium salt is used in the range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore, excellent electrolyte performance can be shown, and lithium ions can be effectively moved.

[0194] When the electrolyte used herein is a solid electrolyte, for example, a solid inorganic electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, a nitride solid electrolyte, or a halide solid electrolyte can be used, and preferably a sulfide solid electrolyte can be used.

[0195] As the material of the sulfide solid electrolyte, a solid electrolyte containing Li, an X element (wherein X is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga and In) and S can be used. Examples of the above-mentioned sulfide solid electrolyte materials include Li2S-P2S5, Li2S-P2S-LiX (wherein X is a halogen element such as I or Cl), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are integers, Z is Ge, Zn or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (wherein p and q are integers, and M is P, Si, Ge, B, Al, Ga or In), etc.

[0196] The solid electrolyte, preferably a sulfide-based solid electrolyte, may be in an amorphous state, a crystalline state, or a mixed state of the amorphous state and the crystalline state.

[0197] Examples of materials for oxide-based solid electrolytes include Li7La3Zr2O 12 , Li 7-x Ln3Z 1-x Nb x O 12 , Li 7- 3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3、Li 1+x Al x Ti 2-x (PO4)3、Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, Li3+x PO 4-x N x (LiPON), Li 2+2x Zn 1-x GeO4(LISICON), etc.

[0198] The solid electrolyte may be arranged between the positive electrode and the negative electrode as a separate layer (solid electrolyte layer). In addition, the solid electrolyte may be partially contained in the positive electrode active material layer of the positive electrode independently of the solid electrolyte layer, or the solid electrolyte may be partially contained in the negative electrode active material layer of the negative electrode independently of the solid electrolyte layer.

[0199] In addition to the above electrolyte components, the electrolyte may further include one or more additives such as halogenated alkylene carbonate compounds such as bisfluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, etc., for the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity, and increasing the discharge capacity of the battery. In this case, the above additives may be included in an amount of 0.1 wt % to 5 wt % relative to the total weight of the electrolyte.

[0200] As described above, the lithium secondary battery containing the positive electrode active material of the present invention stably shows excellent discharge capacity, output characteristics and life characteristics, and can therefore be used in portable devices such as mobile phones, notebook computers, digital cameras, and electric vehicles such as hybrid electric vehicles (HEV).

[0201] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a prismatic shape, a pouch shape, a coin shape, etc. Also, preferably, the lithium secondary battery can be used not only as a battery cell used as a power source for small devices, but also as a unit battery of a medium or large battery module including a plurality of battery cells.

[0202] According to another aspect of the present invention, a battery module including the above-mentioned lithium secondary battery as a unit cell and / or a battery pack including the same may be provided.

[0203] The battery module or the battery pack can be used as a power tool; an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle and a plug-in hybrid electric vehicle (PHEV); or a power source for one or more medium or large devices in a power storage system.

[0204] Hereinafter, the present invention will be described in more detail by way of examples. However, these examples are only for illustrating the present invention, and the scope of the present invention should not be construed as being limited by these examples.

[0205] Preparation Example 1. Preparation of positive electrode active material

[0206] Preparation Example 1-1. Preparation of the First Lithium Manganese-Based Oxide (A-1)

[0207] (a) Precursor preparation

[0208] An aqueous solution of NiSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:60, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 45°C, and N2 gas was introduced into the reactor while the precursor synthesis reaction was carried out for 5 hours. After the reaction was completed, the Ni 0.4 Mn 0.6 The hydroxide precursor composed of (OH)2 (average particle size is 3.0μm).

[0209] (b) First heat treatment

[0210] The sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the hydroxide precursor obtained in the above step (a) was heat-treated for 5 hours while maintaining 550°C, followed by furnace cooling to obtain a precursor in an oxide state.

[0211] (c) Second heat treatment

[0212] A mixture was prepared by mixing the precursor in an oxide state obtained in the above step (b) with LiOH (lithium / metal molar ratio = 1.28) as a lithium raw material material.

[0213] Next, the sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the mixture was heat-treated for 8 hours while maintaining 900°C, and then furnace-cooled to obtain a first lithium manganese-based oxide (A-1).

[0214] The BET specific surface area of ​​the first lithium manganese-based oxide (A-1) (calculated from the amount of nitrogen adsorbed at liquid nitrogen temperature (77 K) using BELSORP-mino II of Japan BEL Corporation) was measured to be 1.93 m 2 / g.

[0215] Preparation of the first lithium manganese-based oxide (A-2)

[0216] (a) Precursor preparation

[0217] An aqueous solution of NiSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:60, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 45°C, and N2 gas was introduced into the reactor while the precursor synthesis reaction was carried out for 5 hours. After the reaction was completed, the Ni 0.4 Mn 0.6 The hydroxide precursor composed of (OH)2 (average particle size is 3.0μm).

[0218] (b) First heat treatment

[0219] The sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the hydroxide precursor obtained in the above step (a) was heat-treated for 5 hours while maintaining 550°C, and then the furnace was cooled to obtain a precursor in an oxide state.

[0220] (c) Second heat treatment

[0221] A mixture is prepared by mixing the precursor in an oxide state obtained in the above step (b), LiOH as a lithium raw material (molar ratio of lithium / metal other than lithium = 1.28), and LiF weighed so that the fluorine (F) content based on metal elements other than lithium in the above precursor is 1.0 mol%.

[0222] Next, the sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the mixture was heat-treated for 8 hours while maintaining 900°C, and then furnace-cooled to obtain a first lithium manganese-based oxide (A-2).

[0223] The BET specific surface area of ​​the first lithium manganese-based oxide (A-2) (calculated from the nitrogen adsorption at liquid nitrogen temperature (77 K) using BELSORP-mino II of Japan BEL Co., Ltd.) was measured to be 1.72 m 2 / g.

[0224] Preparation of the first lithium manganese-based oxide (A-3)

[0225] (a) Precursor preparation

[0226] An aqueous solution of NiSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:60, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 45°C, and N2 gas was introduced into the reactor while the precursor synthesis reaction was carried out for 5 hours. After the reaction was completed, the Ni 0.4 Mn 0.6 The hydroxide precursor composed of (OH)2 (average particle size is 3.0μm).

[0227] (b) First heat treatment

[0228] The sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the hydroxide precursor obtained in the above step (a) was heat-treated for 5 hours while maintaining 550°C, and then the furnace was cooled to obtain a precursor in an oxide state.

[0229] (c) Second heat treatment

[0230] A mixture is prepared by mixing the precursor in an oxide state obtained in the above step (b), LiOH as a lithium raw material (molar ratio of lithium / metal other than lithium = 1.28), and LiF weighed so that the fluorine (F) content based on metal elements other than lithium in the above precursor is 1.0 mol%.

[0231] Next, the sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the mixture was heat-treated for 8 hours while maintaining 900°C, and then furnace-cooled to obtain a lithium-rich lithium manganese-based oxide.

[0232] (d) Third heat treatment (forming a barrier layer)

[0233] After mixing the lithium manganese-based oxide obtained in the above step (c) and H3BO3 (weighed so that the boron content of the lithium manganese-based oxide based on metal elements other than lithium is 2.0 mol%), the temperature is raised to 400°C at a rate of 4.4°C / min while maintaining an O2 atmosphere in a sintering furnace, and then heat-treated for 8 hours, classified and pulverized to obtain a first lithium manganese-based oxide (A-3) having a barrier layer containing a boron-containing compound formed on the surface.

[0234] The BET specific surface area of ​​the first lithium manganese-based oxide (A-3) (calculated from the amount of nitrogen adsorbed at liquid nitrogen temperature (77 K) using BELSORP-mino II of Japan BEL Co., Ltd.) was measured to be 1.43 m 2 / g.

[0235] Preparation of the first lithium manganese-based oxide (A-4)

[0236] (a) Precursor preparation

[0237] An aqueous solution of NiSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:60, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 45°C, and N2 gas was introduced into the reactor while the precursor synthesis reaction was carried out for 5 hours. After the reaction was completed, the Ni 0.4 Mn 0.6 The hydroxide precursor composed of (OH)2 (average particle size is 3.0μm).

[0238] (b) First heat treatment

[0239] The sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the hydroxide precursor obtained in the above step (a) was heat-treated for 5 hours while maintaining 550°C, and then the furnace was cooled to obtain a precursor in an oxide state.

[0240] (c) Second heat treatment

[0241] A mixture is prepared by mixing the precursor in an oxide state obtained in the above step (b), LiOH as a lithium raw material (molar ratio of lithium / metal other than lithium = 1.28), and LiF weighed so that the fluorine (F) content based on metal elements other than lithium in the above precursor is 0.75 mol%.

[0242] Next, the sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the mixture was heat-treated for 8 hours while maintaining 900°C, and then furnace-cooled to obtain a lithium-rich lithium manganese-based oxide.

[0243] (d) Third heat treatment (forming a barrier layer)

[0244] After mixing the lithium manganese-based oxide obtained in the above step (c) and H3BO3 (weighed so that the boron content of the lithium manganese-based oxide based on metal elements other than lithium is 2.0 mol%), the temperature is raised to 400°C at a rate of 4.4°C / min while maintaining an O2 atmosphere in a sintering furnace, and then heat-treated for 8 hours, classified and pulverized to obtain a first lithium manganese-based oxide (A-4) having a barrier layer containing a boron-containing compound formed on the surface.

[0245] The BET specific surface area of ​​the first lithium manganese-based oxide (A-4) (calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77 K) using BELSORP-mino II of Japan BEL Co., Ltd.) was measured to be 1.50 m 2 / g.

[0246] Preparation of the Second Lithium Manganese-Based Oxide (B-1)

[0247] (a) Precursor preparation

[0248] A mixed aqueous solution of NiSO4·6H2O and MnSO4·H2O in a molar ratio of 40:60, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 45°C, and N2 gas was introduced into the reactor while the precursor synthesis reaction was carried out for 24 hours. After the reaction was completed, the Ni 0.4 Mn 0.6 The hydroxide precursor composed of (OH)2 (average particle size is 12.0μm).

[0249] (b) First heat treatment

[0250] The sintering furnace in an O2 atmosphere is heated at a rate of 2°C / min, and then the hydroxide precursor obtained in the above step (a) is heat-treated for 5 hours while maintaining 550°C, and then the furnace is cooled to obtain a precursor in an oxide state.

[0251] (c) Second heat treatment

[0252] A mixture was prepared by mixing the precursor in an oxide state obtained in the above step (b) with LiOH (lithium / metal molar ratio = 1.28) as a lithium raw material material.

[0253] Next, the sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the mixture was heat-treated for 8 hours while maintaining 900°C, and then furnace-cooled to obtain a second lithium manganese-based oxide (B-1).

[0254] The BET specific surface area of ​​the second lithium manganese-based oxide (B-1) (calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77 K) using BELSORP-mino II of Japan BE L Co., Ltd.) was measured to be 2.38 m 2 / g.

[0255] Preparation of the Second Lithium Manganese-Based Oxide (B-2)

[0256] (a) Precursor preparation

[0257] A mixed aqueous solution of NiSO4·6H2O and MnSO4·H2O in a molar ratio of 40:60, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 45°C, and N2 gas was introduced into the reactor while the precursor synthesis reaction was carried out for 24 hours. After the reaction was completed, the Ni 0.4 Mn 0.6 The hydroxide precursor composed of (OH)2 (average particle size is 12.0μm).

[0258] (b) First heat treatment

[0259] The sintering furnace in an O2 atmosphere is heated at a rate of 2°C / min, and then the hydroxide precursor obtained in the above step (a) is heat-treated for 5 hours while maintaining 550°C, and then the furnace is cooled to obtain a precursor in an oxide state.

[0260] (c) Second heat treatment

[0261] A mixture is prepared by mixing the precursor in an oxide state obtained in the above step (b), LiOH as a lithium raw material (molar ratio of lithium / metal other than lithium = 1.28), and LiF weighed so that the fluorine (F) content based on metal elements other than lithium in the above precursor is 1.0 mol%.

[0262] Next, the sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the mixture was heat-treated for 8 hours while maintaining 900°C, and then furnace-cooled to obtain a second lithium manganese-based oxide (B-2).

[0263] The BET specific surface area of ​​the second lithium manganese-based oxide (B-2) (calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77 K) using BELSORP-mino II of Japan BE L Co., Ltd.) was measured to be 0.86 m 2 / g.

[0264] Preparation of the second lithium manganese-based oxide (B-3)

[0265] (a) Precursor preparation

[0266] A mixed aqueous solution of NiSO4·6H2O and MnSO4·H2O in a molar ratio of 40:60, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 45°C, and N2 gas was introduced into the reactor while the precursor synthesis reaction was carried out for 24 hours. After the reaction was completed, the Ni 0.4 Mn 0.6 The hydroxide precursor composed of (OH)2 (average particle size is 12.0μm).

[0267] (b) First heat treatment

[0268] The sintering furnace in an O2 atmosphere is heated at a rate of 2°C / min, and then the hydroxide precursor obtained in the above step (a) is heat-treated for 5 hours while maintaining 550°C, and then the furnace is cooled to obtain a precursor in an oxide state.

[0269] (c) Second heat treatment

[0270] A mixture is prepared by mixing the precursor in an oxide state obtained in the above step (b) with LiOH (molar ratio of lithium / metal other than lithium=1.28) as a lithium raw material material.

[0271] Next, the sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the mixture was heat-treated for 8 hours while maintaining 900°C, and then furnace-cooled to obtain a lithium-rich lithium manganese-based oxide.

[0272] (d) Third heat treatment (forming a barrier layer)

[0273] After mixing the above-mentioned lithium manganese-based oxide obtained in the above-mentioned step (c) and H3BO3 (weighed so that the boron content based on metal elements other than lithium in the above-mentioned lithium manganese-based oxide is 2 mol%), the temperature is raised to 400°C at a rate of 4.4°C / min while maintaining an O2 atmosphere in a sintering furnace, and then heat-treated for 8 hours, classified and pulverized to obtain a second lithium manganese-based oxide (B-3) having a barrier layer containing a boron-containing compound formed on the surface.

[0274] The BET specific surface area of ​​the second lithium manganese-based oxide (B-3) (calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77 K) using BELSORP-mino II of Japan BEL Co., Ltd.) was measured to be 1.81 m 2 / g.

[0275] Preparation Example 2. Preparation of positive electrode active material

[0276] A positive electrode active material having a monomodal particle size distribution or a bimodal particle size distribution was prepared by mixing the first lithium manganese-based oxide and the second lithium manganese-based oxide prepared according to Preparation Example 1 at a weight ratio shown in Table 1 below.

[0277] In the case of a positive electrode active material having a bimodal particle size distribution, the absolute value of the difference (ΔBET) in BET specific surface area between the first lithium composite oxide as small particles and the second lithium composite oxide as large particles is calculated.

[0278] Table 1

[0279]

[0280] Preparation Example 3. Fabrication of a lithium secondary battery (half-cell)

[0281] 90 wt % of each positive electrode active material prepared according to Preparation Example 2, 4.5 wt % of carbon black and 5.5 wt % of PVDF binder were dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum film with a thickness of 15 μm and vacuum dried at 135° C. to prepare a positive electrode for a lithium secondary battery.

[0282] Relative to the above-mentioned positive electrode, lithium foil is used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25μm) is used as a separation membrane, and an electrolyte solution containing LiPF6 at a concentration of 1.15M in a solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate mixed in a volume ratio of 2:4:4 is used to prepare a half-cell.

[0283] Preparation Example 4. Preparation of lithium secondary battery (full battery)

[0284] 90 wt % of each positive electrode active material prepared according to Preparation Example 2, 4.5 wt % of carbon black and 5.5 wt % of PVDF binder were dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum film with a thickness of 15 μm and vacuum dried at 135° C. to prepare a positive electrode for a lithium secondary battery.

[0285] Relative to the above-mentioned positive electrode, a graphite electrode was used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as a separation membrane, and a full battery was prepared using an electrolyte solution in which LiP F6 was present at a concentration of 1.15 M in a solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate mixed in a volume ratio of 2:4:4.

[0286] Experimental Example 1. Compression density measurement of positive electrode active material

[0287] Each positive electrode active material prepared according to Preparation Example 2 was weighed to 3 g using a granulator, and a pressure of 4.5 tons was applied for 5 seconds, and then the compression density was measured.

[0288] The above measurement results are shown in Table 2 below.

[0289] Table 2

[0290] Pressure conditions 4.5 tons unit g / cc Comparative Example 1 2.39 Comparative Example 2 2.47 Comparative Example 3 2.66 Comparative Example 4 2.69 Comparative Example 5 2.74 Comparative Example 6 2.82 Example 1 2.93 Example 2 2.90

[0291] Referring to the results in Table 2, it was confirmed that the compression density of the positive electrode active material having a bimodal particle size distribution was higher than the compression density of the positive electrode active materials according to Comparative Examples 1 and 2 having a unimodal particle size distribution.

[0292] In addition, it can be confirmed that the positive electrode active materials according to Examples 1 and 2, which are positive electrode active materials using halogen-doped small particles and having barrier layers formed on the surfaces of the small particles and large particles, have higher compression density than other positive electrode active materials having a bimodal particle size distribution.

[0293] Experimental Example 2. Evaluation of electrochemical performance of lithium secondary battery (half-cell)

[0294] The lithium secondary battery (half cell) prepared according to Preparation Example 3 was subjected to a charge / discharge experiment using an electrochemical analyzer (Toyo, Toscat-3100) at 25° C., a voltage range of 2.0 V to 4.6 V, and a discharge rate of 0.1 C to 5.0 C to measure the initial discharge capacity, the capacity per unit volume, and the rate performance (discharge capacity ratio; rate capability, C-rate).

[0295] The above capacity per unit volume was calculated by multiplying the initial discharge capacity by the compression density (4.5 tons compression density in Table 4).

[0296] The above measurement results are shown in Table 3 below.

[0297] Table 3

[0298]

[0299] Referring to the results in Table 3, it was confirmed that the capacity per unit volume of the positive electrode active material having a bimodal particle size distribution was higher than the capacity per unit volume of the positive electrode active materials according to Comparative Examples 1 and 2 having a unimodal particle size distribution.

[0300] In addition, the capacity per unit volume of the positive electrode active material according to Examples 1 and 2, which is a positive electrode active material using halogen-doped small particles and forming a barrier layer on the surface of the small particles and the large particles, is greater than the capacity per unit volume of other positive electrode active materials having a bimodal particle size distribution. In addition, it is confirmed that the positive electrode active materials according to Examples 1 and 2 exhibit improved discharge capacity and rate performance compared to other positive electrode active materials having a bimodal particle size distribution.

[0301] Experimental Example 3. Evaluation of electrochemical performance of lithium secondary battery (full battery)

[0302] For the lithium secondary battery (full battery) prepared in Preparation Example 4 using the positive electrode active material according to Example 1, Comparative Example 5 and Comparative Example 6, an electrochemical analyzer (Toyo, Toscat-3100) was used to complete 6 cycles of formation at 25°C, a voltage range of 2.0V to 4.6V and 0.2C / 0.2C, and then charged / discharged 500 times at 25°C, a voltage range of 2.0V to 4.6V and 1C / 1C. The initial (first cycle) discharge capacity, the ratio of the discharge capacity of the 100th cycle, the 300th cycle, and the 500th cycle relative to the initial discharge capacity (cycle capacity retention; capacity retention) were measured.

[0303] The above measurement results are shown in Table 4 below.

[0304] Table 4

[0305]

[0306] Referring to the results in Table 4, it can be confirmed that the cycle capacity retention rates of Comparative Examples 5 and 6 are lower than that of Example 1. It is estimated that the above results are due to the abnormal resistance of the negative electrode as the transition metal dissolves from the lithium manganese-based oxide, thereby accelerating the life degradation of the lithium secondary battery.

[0307] Therefore, it can be confirmed that the positive electrode active material according to Example 1 is more suitable for use as a lithium secondary battery requiring a long life.

[0308] Experimental Example 4. Experiment on the dissolution of transition metals

[0309] For the lithium secondary battery (full battery) prepared in Preparation Example 4 using the positive electrode active material according to Example 1, Comparative Example 5 and Comparative Example 6, an electrochemical analyzer (Toyo, Toscat-3100) was used to complete 6 cycles of formation at 25°C, a voltage range of 2.0V to 4.6V, and 0.2C / 0.2C, and then the full battery was charged / discharged for 2 cycles at 25°C, a voltage range of 2.0V to 4.6V, and 0.05C / 0.05C for stabilization. Then, after the full battery was disassembled, the negative electrode was cleaned with a diethyl carbonate solvent, vacuum dried at 60°C, and then recovered.

[0310] Only the negative electrode active material was separated from the recovered copper foil (current collector) of the recovered negative electrode, and the separated negative electrode active material was subjected to ICP analysis to measure the contents of manganese and nickel contained in the negative electrode active material.

[0311] In addition, for the lithium secondary battery (full battery) prepared in Preparation Example 4 using the positive electrode active material according to Example 1, Comparative Example 5 and Comparative Example 6, an electrochemical analyzer (Toyo, Toscat-3100) was used to complete 6 cycles of formation at 25°C, a voltage range of 2.0V to 4.6V and 0.2C / 0.2C, and then charged / discharged 500 times at 25°C, a voltage range of 2.0V to 4.6V and 1C / 1C. Subsequently, the full battery was stabilized by performing secondary cycle charge / discharge at 25°C, a voltage range of 2.0V to 4.6V and 0.05C / 0.05C. Then, after the full battery was disassembled, the negative electrode was cleaned with a diethyl carbonate solvent, vacuum dried at 60°C, and then recovered.

[0312] Only the negative electrode active material was separated from the recovered copper foil (current collector) of the recovered negative electrode, and the separated negative electrode active material was subjected to ICP analysis to measure the contents of manganese and nickel contained in the negative electrode active material.

[0313] The above measurement results are shown in Table 5 below.

[0314] Table 5

[0315]

[0316] Referring to the results in Table 5 above, as expected in Experimental Example 4, it can be confirmed that the low cycle capacity retention rates of Comparative Examples 5 and 6 compared with Example 1 are due to the increase in the transition metal content deposited on the negative electrode active material after formation and / or after 500 charge / discharge cycles.

[0317] Although the embodiments of the present invention are described above, those skilled in the art will understand that various modifications and changes can be made to the present invention by adding, modifying, deleting, increasing, etc., without departing from the scope of the idea of ​​the present invention as described in the claims, and these also fall within the scope of the rights of the present invention.

Claims

1. A positive electrode active material, which is a positive electrode active material having a bimodal particle size distribution including a first lithium manganese-based oxide and a second lithium manganese-based oxide having different average particle sizes. The positive electrode active material is characterized in that, the first lithium manganese-based oxide and the second lithium manganese-based oxide are oxides formed by solid solution of a phase containing at least lithium and manganese and belonging to the C2 / m space group and a phase belonging to the R-3m space group, at least a part of the oxygen present in the first lithium manganese-based oxide is substituted by a halogen, a blocking layer exists on the surfaces of the first lithium manganese-based oxide and the second lithium manganese-based oxide.

2. The positive electrode active material according to claim 1, characterized in that, the first lithium manganese-based oxide and the second lithium manganese-based oxide are composite oxides including lithium, manganese and a transition metal.

3. The positive electrode active material according to claim 2, characterized in that, the transition metal is at least one selected from nickel, cobalt and aluminum.

4. The positive electrode active material according to claim 1, characterized in that, the first lithium manganese-based oxide is doped with fluorine.

5. The positive electrode active material according to claim 1, characterized in that, the first lithium manganese-based oxide is represented by the following Chemical Formula 1 or Chemical Formula 1-1: [Chemical Formula 1] He(He a M1 x M2 y )O 2-b X b (wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, and M2 does not overlap with M1, X is a halogen capable of substituting at least a part of the oxygen present in the lithium manganese-based oxide, 0 < a ≤ 0.7, 0 < b ≤ 0.1, 0 < x ≤ 1, 0 ≤ y < 1, 0 < x + y ≤ 1) [Chemical Formula 1-1] rLi2MnO 3-b" X' b" ·(1-r)Li a' M1 x' M2 y' O 2-b' X b' (wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, and M2 does not overlap with M1, X and X' are halogens capable of substituting at least a part of the oxygen present in the lithium manganese-based oxide, 0 < r ≤ 0.7, 0 < a' ≤ 1, 0 ≤ b' ≤ 0.1, 0 ≤ b" ≤ 0.1, 0 < x' ≤ 1, 0 ≤ y' < 1, 0 < x' + y' ≤ 1, but b' and b" are not both 0).

6. The positive electrode active material according to claim 1, characterized in that, the average particle size of the first lithium manganese-based oxide is 2 μm to 6 μm.

7. The positive electrode active material according to claim 1, characterized in that, The BET specific surface area of ​​the first lithium manganese-based oxide is 1.0 m 2 / g to 1.8m 2 / g.

8. The positive electrode active material according to claim 1, characterized in that, the second lithium manganese-based oxide is represented by the following Chemical Formula 2: [Chemical Formula 2] <h2 style=";text-align:left;direction:ltr">rLi2MnO3·(1-r)Li<h2 style=";text-align:left;direction:ltr"> a' <h2 style=";text-align:left;direction:ltr"> M1<h2 style=";text-align:left;direction:ltr"> x' <h2 style=";text-align:left;direction:ltr"> M2<h2 style=";text-align:left;direction:ltr"> y' <h2 style=";text-align:left;direction:ltr"> O2 (wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, and M2 and M1 do not repeat, 0 <r≤0.7、0<a'≤1、0<x'≤1、0≤y'<1、0<x'+y'≤1)。 9. The positive electrode active material according to claim 1, characterized in that The second lithium manganese-based oxide has an average particle size of 7 μm to 14 μm.

10. The positive electrode active material according to claim 1, characterized in that The BET specific surface area of ​​the second lithium manganese-based oxide is 1.5 m 2 / g to 2.3m 2 / g.

11. The positive electrode active material according to claim 1, characterized in that The barrier layer includes an oxide containing at least one element selected from B, Si, P and Ge.

12. The positive electrode active material according to claim 11, characterized in that The barrier layer includes an oxide represented by the following chemical formula 3: [Chemical formula 3] <h2 style=";text-align:left;direction:ltr">zLi2O*(1-z)M3<h2 style=";text-align:left;direction:ltr"> d <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> e (in, M3 is at least one element selected from B, Si, P and Ge, 0 <z≤0.8、0<d≤10、0<e≤10)。 13. The positive electrode active material according to claim 11, characterized in that The barrier layer comprises B2O3, H α B β O γ (0<α<10, 0<β<10, 0<γ<20) and Li α' B β' O γ' At least one boron-containing compound selected from the group consisting of (0<α'<10, 0<β'<10, 0<γ'<20).

14. The positive electrode active material according to claim 1, characterized in that The barrier layer exists on the surfaces of the first lithium manganese-based oxide and the second lithium manganese-based oxide in the form of a film having a thickness of 1 nm to 300 nm.

15. The positive electrode active material according to claim 1, characterized in that In the positive electrode active material, a weight ratio of the first lithium manganese-based oxide to the second lithium manganese-based oxide is 10:90 to 80:

20.

16. A positive electrode, characterized in that: The positive electrode active material comprises the positive electrode active material according to any one of claims 1 to 15.

17. A lithium secondary battery, characterized in that: Comprising the positive electrode as claimed in claim 16.